Literature Review Of The Influence Of Technology On The Organizational Behavior Of Manufacturing Companies In Indonesia - Sunyoto, Agus Bambang; Rachman, Tutut Arif; Sopiah (PT Maju Malaqbi Makkarana, 2025)
This research aims to synthesize publications related to the use of technology in manufacturing companies in Indonesia on organizational behavior. By using the SLR method with PRISMA steps. Articles filtered from the journals of Emerald Insight, Sage Journals, Science Direct, and Taylor & Francis with topics and keywords of organizational behavior, managers, technology use, and manufacturing companies in Indonesia published between 2020 and 2025 totaled 4,262 articles. After elimination according to the criteria, only 20 articles were considered and extracted. The results of this study are that technological advances and the use of technology in manufacturing companies affect organizational behavior. Two things were found from this synthesis, the first is organizational behavior with technology that increases open innovation and sustainability-oriented organizational behavior, especially sustainability in the environment, and the second is that organizations are oriented towards digitalization, namely with digital programs or programs that make their work more effective and efficient. This research can be used by manufacturing as an evaluation related to the use of technology in manufacturing companies and the basis of knowledge to improve employee skills and knowledge, in addition to it can be used as a follow-up research material to further explore the influence of organizational behavior on large-scale manufacturing companies.